Enhancing laccase production by white-rot fungus Funalia floccosa LPSC 232 in co-culture with Penicillium commune GHAIE86 - Rodríguez, Rosario Díaz; Heredia, Gabriela; Siles, José A; Jurado, Miguel; Saparrat, Mario Carlos Nazareno; García-Romera, Inmaculada; Sampedro, Inmaculada (Folia microbiologica, 2019)
To obtain enzymatic preparations with higher laccase activity levels from Funalia floccosa LPSC 232, available for use in several applications, co-cultures with six filamentous microfungi were tested. A laccase non-producing soil fungus, identified as Penicillium commune GHAIE86, showed an outstanding ability to increase laccase activity (3-fold as compared to that for monoculture) when inoculated in 6-day-old F. floccosa cultures. Maximum laccase production with the F. floccosa and P. commune co-culture reached 60 U/mL, or twice that induced by chemical treatments alone. Our study demonstrated that co-culture with soil fungi might be a promising method for improving laccase production in F. floccosa. Although the enhancement of laccase activity was a function of P. commune inoculation time, two laccase isoenzymes produced by F. floccosa remained unchanged when strains were co-cultured. These data are compatible with the potential of F. floccosa in agricultural applications in soil, whose enzyme machinery could be activated by soil fungi such as P. commune.
Keywords: kokultivační techniky; půdní mikrobiologie; Microbial Interactions; Time Factors; lakasa; časové faktory; Polyporales; Laccase; Colony Count, Microbial; počet mikrobiálních kolonií; mikrobiální interakce; Coculture Techniques; Polyporaceae; Penicillium; Soil Microbiology